Weak discontinuities in a dissociating gas - Sharma V.D. (My University, 2025)
The effects of non-equilibrium dissociation and that of the wave front curvature on the propagation of weak discontinuities headed by wave fronts of arbitrary shape and their consequent formation into shock waves are examined. It is found that all compressive waves, except in one special case of converging waves, grow without bound only if the magnitude of the initial discontinuity associated with the wave exceeds a critical value. It is shown that, in this special case, the stabilizing influence of curvature for converging waves is not strong enough to overcome the instabilities associated with the gasdynamic phenomenon involved. © 1981 Springer-Verlag.